Organizing a community-based program for special children in Cainta, Rizal - Patriarca, Elsa C.
The study investigated the strengths and weaknesses, threats, opportunities, and best practices perceived by various stakeholders in the community as bases for organizing a community-based SPED program in Cainta, Rizal. It also integrated steps and processes used by successful community-based rehabilitation programs here in the Philippines and abroad, and formulated a blueprint for a program that can be organized and implemented later in the said community. The respondents included parents of special children, barangay officials, local government officials, civic organizations, parish priest, and social workers.It is envisioned that expanding the community-based program to reach out to other communities can result from gathered best practices and opportunities perceived by stakeholders.